VARIASI BUNYI BAHASA BUGIS DI SULAWESI SELATAN - Johar Amir; Ambo Dalle; Shafarina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines various sound changes and lexical variations in the Bugis language that occur in Pinrang Regency, Soppeng Regency, Sidrap Regency, and Bone Regency. This study employed a qualitative research method that produced descriptive data, with the research subjects consisting of 12 male and female informants aged between 20 and 60 years. The research instruments included the researcher as the primary instrument and an additional instrument in the form of 200 questionnaire items containing sound variations. The data collection techniques consisted of observation, participant observation, non-participant observation, recording, and note-taking, which were subsequently analyzed using two techniques, namely the determinant element sorting technique and the comparative method. The results of the study show that there are eight forms of sound variation in the Bugis language in several regencies. These variations include (1) the sound change (e-i) into (i-e), (2) the sound change (ǝ) into (a), (3) the sound change (b) into (w), (4) the sound change (p) into (f), (5) the sound change (?) into (:), (6) the addition of an initial phoneme, (7) the addition of a final phoneme, and (8) consonant alternation. This study concludes that the Bugis vocabulary does not have absolute sounds; the pronunciation of the Bugis language differs in each regency, influenced by speech habits, geographical location, social and economic conditions, and the cultural heritage of the local community.